L'offre de diplômes professionnels de l'Éducation nationale en France : injonctions contradictoires - Fabienne Maillard (Les éditions de la Maison des sciences de l'Homme, 2005)
This paper examines the underpinnings of professional qualifications in France. The evolution in that field results from two elements: the choice by the Ministry of Education and its partners of a constructivist perspective and its ambivalence about vocational training and certification. The Ministry tends to equate professional qualifications with professional skills, assigning them various purposes and using them as a way to regulate student population flows. The current superimposition of definitions and principles emphasizes the discontinuity of institutional policies and their very contradictions.